2015
DOI: 10.1177/0960327115569808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alendronate and pamidronate on apoptosis and cell proliferation in cultured primary human gingival fibroblasts

Abstract: Data arising from the recent literature directed the researchers to study on the degree and extent of bisphosphonate toxicity on oral mucosa in further detail. The aim of this study is to determine the half maximal inhibitory concentration of pamidronate (PAM) and alendronate (ALN) on human gingival fibroblasts in vitro using 3-[4.5-thiazol-2-yl]-2.5-diphenyltetrazolium bromide (MTT) assay and to evaluate the effects of both agents on the proliferation and apoptotic indices. Cells used in the study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
4
16
0
1
Order By: Relevance
“…One-way ANOVA analysis was applied to determine the statistical differences in rapport with control/DMSO followed by Dunnett's multiple comparisons posttest (** p<0.01 and **** p< 0.0001). alendronate -F on human primary gingival fibroblasts was also shown by other groups of research [21][22][23], data that are in agreement with these results. Stimulation of human stem cells derived from the gingiva with risedronate in the range of 1-10 µM led to changes in cells morphology and a reduced viability [24], findings that confirm our results.…”
Section: Bisphosphonates Impair Human Primar Y Gingival Fibroblasts -supporting
confidence: 91%
See 1 more Smart Citation
“…One-way ANOVA analysis was applied to determine the statistical differences in rapport with control/DMSO followed by Dunnett's multiple comparisons posttest (** p<0.01 and **** p< 0.0001). alendronate -F on human primary gingival fibroblasts was also shown by other groups of research [21][22][23], data that are in agreement with these results. Stimulation of human stem cells derived from the gingiva with risedronate in the range of 1-10 µM led to changes in cells morphology and a reduced viability [24], findings that confirm our results.…”
Section: Bisphosphonates Impair Human Primar Y Gingival Fibroblasts -supporting
confidence: 91%
“…Another study conducted by Soydan et al [22] demonstrated the toxic effects of Alendronate (Fosamax) and PAM on human gingival fibroblasts, characterized by significant changes in the apoptotic and proliferative indices leading to an in vitro faulty epithelisation of the oral mucosa. The apoptotic index of the PAM group was significantly higher than the alendronate group for all concentrations, especially at 24 h of incubation (p <0.05).…”
Section: Bisphosphonates Impair Human Primar Y Gingival Fibroblasts -mentioning
confidence: 99%
“…Our results showed that F and A become cytotoxic even at low concentrations as 1.5 µM (see Figure 1B) and also cells morphology was altered (see Figures 3 and 4), whereas O and Z had no cytotoxic effects at the concentrations tested (1.5; 2.5; 5 and 10 µM) (see Figure 1A). The cytotoxic effect of alendronate -F on human primary gingival fibroblasts was also shown by other groups of research [27,28,29], data that are in agreement with these results. Stimulation of human stem cells derived from the gingiva with risedronate in the range of 1-10 µM led to changes in cells morphology and a reduced viability [30], findings that confirm our results.…”
Section: Bisphosphonates Decrease Human Primary Gingival Fibroblasts supporting
confidence: 90%
“…e drug accumulating e ect on di erent sites of skeletal bones might play a part in the site-speci c e ect of MRONJ. Studies showed that BPs exerted direct toxic e ects on oral epithelial cells and broblasts when accumulated at su cient concentrations in bone tissue [19][20][21][22]. is toxic e ect further led to delayed so tissue healing and secondary infection and resulted in necrosis of the underlying bone.…”
Section: Discussionmentioning
confidence: 99%